Compact planar reconfigurable UWB‐MIMO antenna with on‐demand worldwide interoperability for microwave access/wireless local area network rejection. Issue 10 (15th May 2019) - Mathur, Rohit; Dwari, Santanu
Abstract : In this study, a compact ultrawideband (UWB) multiple‐input–multiple‐output (MIMO) antenna with reconfigurable band notch characteristics is presented. The key feature of the antenna is its novel dual‐band notch technique which blocks worldwide interoperability for microwave access or wireless local area network band interference. The UWB‐MIMO property is achieved by two square monopoles separated by grounded multi‐branch T‐shaped stub. The reconfigurable dual‐band notch operation is performed by PIN diodes integrated in a parasitic resonant structure in the ground plane. The antenna has a compact size of 40 × 20 mm 2, with the operating frequency band of 3–11 GHz, where port isolation is better than 15 dB. The MIMO performance is ensured by calculating envelope correlation coefficient for the isotropic, indoor and outdoor environment.